GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION TO ANALYZE LANDSLIDE PRONE DISASTER ZONE IN JEMBER REGENCY EAST JAVA - Fahmi Arif Kurnianto; Bejo Apriyanto; Elan Artono Nurdin; Fahrudi Ahwan Ikhsan; Rosmadi Bin Fauzi (Geosfera Indonesia, 2018)
Jember regency has several areas that are morphology of folding hills and mountain folds. The part of landslide prone zone is closely related to the slope of the slope. Areas with a sloping slope of more than 15Âº need attention to the possibility of a landslide disaster. Interconnection contacts with weathering of rocks, settlements and land cover also affect the landslide potential. The existence of Ijen Volcano that produces volcanic rock deposits that are generally not yet unified will increase the potential for landslides in Jember Regency. Landslide has occurred one of them on Gunung Gumitir Street which is the main route of Surabaya-Jember-Banyuwangi traffic. In May 2016 this street is hit by landslide, so the flow of traffic through this lane is paralyzed and must be diverted to a further path, which rotates to Situbondo City. The transfer of this pathway resulted in a loss to the local community and who crossed the path.The occurrence of landslide disaster shows that Jember Regency area is vulnerable and potentially return to landslide. Therefore there is a need for a solution to solve this problem. One solution to solve the problem is by utilizing Geographic Information System (GIS) application. The purpose of this research is to analyze zonation prone to landslide in jember district. The design of the research is Geographic Information System overlay analysis. This design combines several parameters in the determination of landslide-prone zones. This design combines several parameters in the determination of landslide-prone zones. The parameter used in this research is (1) land use, (2) topography, and (3) soil.Based on the research results, it can be known zone with highest to lowest vulnerability level. Zone with very high level of vulnerability is located in Panti sub-district, Sumberbaru, Sukorambi, Dyke, Silo and Jelbuk. The zones have similar characteristics that include (1) soil type of andosol, (2) clay texture, (3) uncompacted rock, (4) slope of 30â°-40â° (steep and very steep), and (5) land use for settlements and plantations. Keyword: landslide disaster, jember regency, Geographic Information System Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License